Feeding Ecology Drives Lead Exposure of Facultative and Obligate Avian Scavengers in the Eastern United States. (22nd March 2020) - Slabe, Vincent A.; Anderson, James T.; Cooper, Jeff; Miller, Tricia A.; Brown, Bracken; Wrona, Anna; Ortiz, Patricia; Buchweitz, John; McRuer, Dave; Dominguez‐Villegas, Ernesto; Behmke, Shannon; Katzner, Todd
Abstract: Lead poisoning of scavenging birds is a global issue. However, the drivers of lead exposure of avian scavengers have been understood from the perspective of individual species, not cross‐taxa assemblages. We analyzed blood ( n = 285) and liver ( n = 226) lead concentrations of 5 facultative (American crows [ Corvus brachyrhynchos ], bald eagles [ Haliaeetus leucocephalus ], golden eagles [ Aquila chrysaetos ], red‐shouldered hawks [ Buteo lineatus ], and red‐tailed hawks [ Buteo jamaicensis ]) and 2 obligate (black vultures [ Coragyps atratus ] and turkey vultures [ Cathartes aura ] avian scavenger species to identify lead exposure patterns. Species and age were significant ( α < 0.05) predictors of blood lead exposure of facultative scavengers; species, but not age, was a significant predictor of their liver lead exposure. We detected temporal variations in lead concentrations of facultative scavengers (blood: median = 4.41 µg/dL in spring and summer vs 13.08 µg/dL in autumn and winter; p = <0.001; liver: 0.32 ppm in spring and summer vs median = 4.25 ppm in autumn and winter; p = <0.001). At the species level, we detected between‐period differences in blood lead concentrations of bald eagles ( p = 0.01) and red‐shouldered hawks during the winter ( p = 0.001). During summer, obligate scavengers had higher liver lead concentrations than did facultative scavengers (median = 1.76 ppm vs 0.22 ppm; p = <0.001). These data suggest that the feeding ecology of avian scavengers is a determinant of the degree to which they are lead exposed, and they highlight the importance of dietary and behavioral variation in determining lead exposure. Environ Toxicol Chem 2020;39:882–892. © 2020 SETAC